Telephone confirmation of a patient’s intent to be present for elective surgery as a strategy to reduce absenteeism - Avila, Marla Andréia Garcia de; Bocchi, Silvia Cristina Mangini (Revista da Escola de Enfermagem da USP, 2013)
The objective of this quasi-experimental study was to evaluate the impact of telephone confirmation of attendance on the reduction of absenteeism of patients scheduled for elective surgery. The study was conducted at the Surgical Department of the Botucatu School of Medicine for 30 days and included 89 patients. Results showed the effectiveness of the intervention, which reduced absenteeism by 30.0%. Telephone confirmation two days prior to surgery is recommended, thus allowing enough time to place new calls to find patients at home, or schedule another patient in the event the patient cannot be reached. The creation of a service center could provide a communication channel between the institution and patients, and would enable the confirmation of patients' attendance, provide them with the opportunity to ask questions concerning the procedure and provide information regarding impediments to the surgery or preparations needed. The center would require a professional skilled and knowledgeable regarding the service, as it involves providing patients with information about their upcoming surgery during the telephone contact.